2008
DOI: 10.1159/000118381
|View full text |Cite
|
Sign up to set email alerts
|

Acute Neurolupus Manifested by Seizures Is Associated with High Frequency of Abnormal Cerebral Blood Flow Velocities

Abstract: Background: Systemic lupus erythematosus may present with a wide variety of neurological manifestations, which could be related to the presence of vasculopathy and microembolic signals (MES). Objectives: We aimed to determine the prevalence of MES and altered blood flow velocities (BFVs) by transcranial Doppler (TCD) in patients with acute neuropsychiatric lupus erythematosus (NPLE). Methods: Fifteen consecutive patients with acute NPLE (cases) and 30 patients with systemic lupus erythematosus but without acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, in a prospective study with patients followed for a mean of 4.5 years, new ischemic events did not occur more frequently in patients with positive MES at baseline [6]. In addition, in another study conducted by our team, MES were not observed more frequently in patients with acute neurological manifestations, including seizures and stroke, although the number of cases was small [4].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 63%
See 1 more Smart Citation
“…However, in a prospective study with patients followed for a mean of 4.5 years, new ischemic events did not occur more frequently in patients with positive MES at baseline [6]. In addition, in another study conducted by our team, MES were not observed more frequently in patients with acute neurological manifestations, including seizures and stroke, although the number of cases was small [4].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 63%
“…Results from five studies [4,6,11,34,47] show that patients with MES (?) have a stroke more frequently associated: 36/57 than MES (-) patients: 26/ 272, OR: 2.19; 95% CI: 1.63-2.95, P \ 0.001.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…8 The PI is an important haemodynamic parameter that linearly correlates with cerebral microvascular tone, blood flow resistance and impedance. 8 Other studies have evaluated PI in patients with SLE 40,49 and APS 6 and found no differences when compared with healthy volunteers. 6 In our series, patients with APS (either PAPS or SAPS) had a trend to present more intracranial stenosis than healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…6 High MFVs were also found in two other studies in patients with SLE, suggesting the presence of a diffuse cerebral vasculopathy. 48,49 It is well known that other factors could explain higher velocities in patients with SLE rather than only a vasculopathy. Several physiologic variables can impact blood flow velocities measured by TCD, including age, gender, hematocrit levels, body temperature, blood pressure and mental or motor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures are found in 15e20% of SLE patients [70,71]. These can be the result of the disease process, such as lupus vasculitis or acute thrombosis, steroid therapy and its attendant hypertension, or a resulting metabolic problem such as uremia [65] or infection.…”
Section: Clinical Involvement Of the Central Nervous Systemmentioning
confidence: 99%